Study on crosstalk fault model and testing for SoC inter-core interconnects. (1st January 2014) - Shang, Yuling; Li, Chunquan; Li, Cailin; Zhang, Ming
Signal integrity testing for inter-cores in SoC has become an important issue within DSM manufacturing technology and GHz working frequency of VLSI. A new testing method for SoC inter-core interconnects is presented in this paper. Properties and principles are obtained based on analysis of crosstalk characteristics for tri-state and bi-directional interconnects. The reduction algorithm of tri-state and bi-direction interconnect is proposed with the properties and principles above. Primary and secondary factors of crosstalk are analysed based on orthogonal design, and then test vectors for interconnects are generated gradually. Finally experiments are implemented, and simulation results show the effectiveness of this method.